УНИФИЦИРОВАННЫЕ СИСТЕМЫ ОТРАБОТКИ УГЛОВОГО ПОЛОЖЕНИЯ, ПОСТРОЕННЫЕ НА ОСНОВЕ ПРИНЦИПА ПАССИВНОСТИ - Пересада, С.М.; Онанко, А.Ю. (Інститут електродинаміки НАН України, Київ, 2013)
The new unified structure of electromechanical system of angular position control is developed. It includes unified velocity and position regulators which could be used in passivity based control. This structure, as well as standard cascade control system structure, includes a cascade connection of position and velocity regulators, but unlike the latter has detached dynamic control loops. This feature provides hierarchical load torque compensation. The method of unified regulators tuning, which uses normalized transient characteristics, is developed. Efficiency of proposed method is confirmed by the example of synthesis the position control system for synchronous motor with permanent magnets. References 5, figures 4.